Significance of bile-duct changes in schistosomiasis Significado das lesões dos ductos biliares na esquistossomose - Ludmila Oliveira; Zilton A. Andrade (Revista da Sociedade Brasileira de Medicina Tropical, 2005)
Lesions involving the intra-hepatic biliary ducts in schistosomiasis have been reported in the literature, both in mice and man, but there are no data concerning their quantitative, evolutionary or post curative chemotherapeutic aspects on record. In order to obtain such data an investigation on this subject was attempted. Mice infected with 50 Schistosoma mansoni cercariae were submitted to a liver biopsy at the 9th week post-infection, and treated with 400mg/bw praziquantel immediately afterwards. Infected and non-infected controls were submitted to the same procedures. By 19 weeks from cercarial exposure all surviving animals were sacrificed. The biliary ducts were counted on histological sections and the results were expressed as biliary ducts/portal spaces. This quantitative evaluation was compared with that from normal controls and revealed hyperplasia as the main biliary duct change (p<0.007) in schistosomiasis. Hyperplastic changes underwent only mild partial and not statistically significant regression after specific chemotherapy (p>0.05). Infected and untreated animals presented ductal changes that did not differ from those of the treated group. Measurements of serum bilirrubin (total and direct), and gamma-glutamyl-transpeptidase (gamma-GT) did not reveal significant differences when animals from the several groups were compared. Thus, bile ducts exhibit a proliferative response in relation to neighboring S. mansoni injury to portal areas, but although these lesions are histopathologically impressive, they lack a functional or prognostic significance. A literatura registra que os ductos biliares intra-hepáticos são lesados no curso da esquistossomose, tanto experimental como humana, mas não existe avaliação quantitativa de tais lesões nos vários estágios da infecção, nem da sua repercussão funcional ou do seu comportamento frente ao tratamento curativo da parasitose. Para avaliar estes parâmetros, os camundongos com infecção por 50 cercárias do Schistosoma mansoni foram submetidos à biópsia hepática na fase recente da infecção (9 semanas) e, em seguida, os animais foram tratados com praziquantel (400mg/kg pc). Controles infectados e não infectados foram incluídos. Durante a 19ª semana pós-infecção todos os animais foram sacrificados. A contagem dos ductos biliares revelou a presença de uma hiperplasia ductal nos animais infectados em relação aos controles intactos (p<0,007), a qual não regrediu significativamente após a terapia antiparasitária (p>0,05). Animais infectados e não tratados exibiram lesões ductais que não diferiram quantitativa ou qualitativamente dos tratados. As concentrações séricas de bilirrubinas (total e direta) e gama-glutamil-transpeptidase (gama-GT) não mostraram diferenças significativas para os animais dos vários grupos. Em conclusão, os ductos biliares mostram uma resposta proliferativa face às alterações de vizinhança provocadas pelo S. mansoni nos espaços porta mas, embora bem evidentes histopatologicamente, tais lesões carecem de significado funcional ou prognóstico.